Innovative methods for optimization of bone regeneration: mesenhymal bone cells (part 2) (literature review) - Korzh, Mykola; Vorontsov, Petro; Vishnyakova, Iryna; Samoilova, Kateryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: on the base of literature we analyzed different methods of mesenhymal stem cells using for optimization of bone regeneration. Methods: we reviewed publications for the last 90 years from electronic data base PubMed, MEDLINE, thesis, articles, manuscripts and other relevant science sources of medical information. We have found more than 200 scientific works, 86 were included for analysis. Results: mesenhymal stem cells have unique abilities — to differentiate into soft tissue cells and multiply in vitro, they possess immune modular and immune suppressive effects. It gives possibility to use them for therapeutic method in regenerative medicine for bone osteogenesis. In review we presented sources of mesenhymal stem cells, ways to get bone marrow puncture and its transplantation, mesenhymal stem cells culturing and possibilities to differentiate them into certain direction. We gave examples of independent and complex (with different implantation materials) using of mesenhymal stem cells. It was shown that mesenhimal stem cells transplantation had positive influence on bone regeneration process, it enlarge osteoblast differentiation, volume of new formed bone tissue and decrease the terms of bone formation. Advantages of mesenhymal stem cells using are minimal invasive procedures and possibility to enlarge number of cells during culturing. But during culturing cells become older and the growth slows down. Creation of bioconstructions on the base of different matrix can facilitate introduction into defect area and create a graft with required shape and size. Choice of material for matrix is debated issue. So further studies of complex bioengineering constructions which will possess peculiarities of bone tissues are go on.